2023
DOI: 10.1155/2023/2894695
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy with Indigo and Indirubin for Ulcerative Colitis via Reinforcing Intestinal Barrier Function

Abstract: Indigo and indirubin, the active molecules of traditional Chinese medicine indigo naturalis, exert therapeutic activity for ulcerative colitis (UC). Indigo and indirubin are isomers and have distinctive profiles in anti-inflammation, immune regulation, intestinal microbiota regulation, oxidative stress regulation, and intestinal mucosal repair for UC treatment. Thus, exploring its combined administration’s integrated advantages for UC is critical. This study is aimed at clarifying the effect and mechanisms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 79 publications
1
9
0
Order By: Relevance
“…Given that (i) MT-102 is an herbal extract including multiple active ingredients, and (ii) SMEDDS-F1 may improve the dissolution of other active and auxiliary substances, SMEDD-F1 may be advantageous for achieving more synergistic effects in therapeutic efficacy compared to isolated indirubin. Xie et al [ 28 ] also support the synergistic effect of multiple components in treating ulcerative colitis. They showed that combined use of indirubin and indigo was more effective in ameliorating DSS-induced colitis by improving the intestinal barrier function compared to indirubin or indigo alone.…”
Section: Resultsmentioning
confidence: 93%
“…Given that (i) MT-102 is an herbal extract including multiple active ingredients, and (ii) SMEDDS-F1 may improve the dissolution of other active and auxiliary substances, SMEDD-F1 may be advantageous for achieving more synergistic effects in therapeutic efficacy compared to isolated indirubin. Xie et al [ 28 ] also support the synergistic effect of multiple components in treating ulcerative colitis. They showed that combined use of indirubin and indigo was more effective in ameliorating DSS-induced colitis by improving the intestinal barrier function compared to indirubin or indigo alone.…”
Section: Resultsmentioning
confidence: 93%
“…At the genus level, OCPs intervention increased the relative abundances of Muribaculaceae_norank, Prevotellaceae _UCG-001, and Alloprevotella . Muribaculaceae_norank, inhibited harmful bacteria and oxidative stress, and improved the inflammation of the intestinal mucosa [ 29 ]. The presence of Prevotellaceae_UCG-001 indicates that there is a close relationship between mediating glucose and lipid metabolism and energy metabolism-related signal regulation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…[Caprifoliaceae; lonicerae japonicae flos], might restore the diversity of gut microbiota, reduce the abundance of Firmicutes and Bacteroidetes , and markedly increase the proportion of Akkermansia ( Zhang et al, 2017 ). Combination therapy with indigo and indirubin was demonstrated to be effective on increasing the amounts of beneficial bacteria, like norank_f_Muribaculaceae and Lactobacillus ( Xie et al, 2023 ).…”
Section: Repairing the Intestinal Biological Barriermentioning
confidence: 99%
“…It was shown that indirubin alone, or combined with isatin, could significantly inhibit DSS-induced CD4 + T cell infiltration in mouse colon, and promote the generation of Foxp3 - expressing regulatory T cells ( Gao et al, 2016 ; Gao et al, 2018 ). Xie et al (2023) showed that combination of indigo and indirubin could reduce the populations of neutrophils, macrophages, and dendritic cells in the lamina propria, and significantly increase the relative quantity of CD335+CD11b+ NK cells.…”
Section: Repairing the Intestinal Immune Barriermentioning
confidence: 99%